PELAKSANAAN PENANAMAN MODAL ASING DI JAWA TENGAH DAN IDENTIFIKASI HAMBATAN SERTA PENYELESAIANNYA - Widiati Dwi Winarni (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
This paper on investment describes the legal system consisting of substance and apparatus. The purposes of this paper are: (1) to study more deeply and explain the process of implementing foreign investment in Indonesia in general and Central Java in particular, in terms of the applicable normative juridical aspects, and (2) to find out the obstacles or obstacles that may occur. in the implementation of the investment. Based on Law Number 25 of 2007 concerning Investment and Central Java Governor Regulation Number 152 of 2010, the general process of implementing foreign investment in Central Java is as follows: (1) Foreign investors submit investment plan files to be carried out to BPMD for registration. in order to obtain an investment permit in Central Java, (2) foreign investors who have obtained permits from BPMD obtain non-fiscal facilities such as Producer Importer Identification Numbers (API-P), Plans for Use of Foreign Workers (RPTKA), Recommendations for Visas to Work, Permits Employing Foreign Workers (IMTA), (3) Investors must establish a PT (Limited Company) in Central Java, and (4) Foreign investors carry out investment activities as planned. Obstacles and settlement of foreign investment in Central Java, among others: (1) obstacles in the form of political stability and security factors. The solution to this obstacle lies with the government; (2) Issues inthe form of “Nominee” Shareholders; (3) Incentives given to foreign investors have the potential to trigger foreign domination of the regional economy; and (4) investment disputes. The settlement of this dispute refers to Article 32 of Law Number 25 of 2007, namely through 4 ways: Deliberation and consensus, Arbitration, Alternative dispute resolution, and Courts.